2013
DOI: 10.4103/0250-474x.119823
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical evaluation of the hypoglycemic effects of extract and fraction of Cassia fistula linn. in alloxan-induced diabetic rats

Abstract: Various extracts of flowers of Cassia fistula Linn (Leguminosae) such as petroleum ether (60-80°), chloroform, acetone, ethanol, aqueous, and crude aqueous extracts and two fractions of ethanol extract were tested for antihyperglycemic activity in glucose-overloaded hyperglycemic rats. The effective antihyperglycemic extracts and fraction were tested for their hypoglycemic activity at two dose levels, 200 and 400 mg/kg, respectively. To confirm their utility in higher models, the effective extracts and fractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 28 publications
(27 reference statements)
3
22
0
Order By: Relevance
“…34,35,47,53 Administration of glibenclamide or C. fistula pod extract at different doses for 60 days in STZ-induced diabetic rats showed significant reduction in the fasting blood glucose levels. These results are parallel with previous reports which have also showed a significant decline in blood glucose levels of diabetic rats after treatment with extract of C. fistula fruit pulp, 42 leaves, 38,54 bark, 34,35 flowers, 40,41 and root. 33 The reduction of fasting blood glucose level by C. fistula pod extract may be due to its many potential bioactive phytochemicals especially rhein glycosides, fistulic acid, sennosides A & B, anthoquinones, flavon-3-ol derivatives, kaempferol, proanthocyanidins like catechin, epiafzelechin, epicatechin and procyanidin 25 and quercetin dehydrates.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…34,35,47,53 Administration of glibenclamide or C. fistula pod extract at different doses for 60 days in STZ-induced diabetic rats showed significant reduction in the fasting blood glucose levels. These results are parallel with previous reports which have also showed a significant decline in blood glucose levels of diabetic rats after treatment with extract of C. fistula fruit pulp, 42 leaves, 38,54 bark, 34,35 flowers, 40,41 and root. 33 The reduction of fasting blood glucose level by C. fistula pod extract may be due to its many potential bioactive phytochemicals especially rhein glycosides, fistulic acid, sennosides A & B, anthoquinones, flavon-3-ol derivatives, kaempferol, proanthocyanidins like catechin, epiafzelechin, epicatechin and procyanidin 25 and quercetin dehydrates.…”
Section: Discussionsupporting
confidence: 92%
“…63 These results are consistent with earlier finding which have also reported significant improvement in oral glucose tolerance in C. fistula extract treated diabetic rats. 41,64 Glycosylated hemoglobin is considered as the most reliable marker of glycemic control in the body. 65 Glycation is a post translational non-enzymatic addition of sugar residues to N-terminal end of the hemoglobin beta chain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Earlier reported by. 27 alkaloid exhibited to glycemic control. According to Jung et al 28 suggested that alkaloid from syzygium malaccense and penares schulzei inhibited glycogen phosphorylase as well as inhibited α-glucosidase both in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 99%